2020
DOI: 10.1007/s13592-020-00808-8
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of hop leaves for development of eco-friendly bee pesticides

Abstract: The bacterium Paenibacillus larvae and the mite Varroa destructor are two of the most severe biotic stressors affecting honeybees and are responsible for American foulbrood and varroosis respectively. To control these pathogens, beekeepers regularly apply synthetic acaricides or antibiotics to parasitized hives. However, antibiotic and acaricide overuse over time leads to resistance in bacteria strains and mite populations respectively, not to mention the residual contamination of bee products with these chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Finally, another plant extract, relying on hop leaves, was shown to contain polyphenols with high miticide effect and low acute toxicity for bees [ 161 , 162 ]. An advantage of hop extracts comes from their antioxidant activity for honeybees, benefiting them if administered orally [ 33 ].…”
Section: Varroa Destructor Chemical and Semi-chemical Control Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, another plant extract, relying on hop leaves, was shown to contain polyphenols with high miticide effect and low acute toxicity for bees [ 161 , 162 ]. An advantage of hop extracts comes from their antioxidant activity for honeybees, benefiting them if administered orally [ 33 ].…”
Section: Varroa Destructor Chemical and Semi-chemical Control Methodsmentioning
confidence: 99%
“…However, preventing them from reproduction or right orientation, as supported by Soroker et al, (2019) [81], would reduce the selective pressure in favour of the most resistant mites. Other works also explained that the use of natural substances could grant a low level of V. destructor infestation, keeping honeybee colonies alive [33]. An integrated pest management strategy should thus, combine all the above ideas.…”
Section: Years Outcome Of Restricted Therapeutic Arsenal: Varroa Destructor Biotype Disparitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also provided some suggestions to improve the composting of hop leaves, such as mixing them with other materials (i.e., cow manure and wheat straw; [ 14 ]). Recently, Iglesias et al [ 15 ] suggested the use of alcoholic extracts of hop leaves to produce an eco-friendly bee pesticide and underlined the influence of genotype on their secondary metabolite content. These biological activities are related to the bioactive compounds present in hop leaves, such as polyphenols [ 16 ].…”
Section: Introductionmentioning
confidence: 99%